2017
DOI: 10.1007/s10461-017-1853-z
|View full text |Cite
|
Sign up to set email alerts
|

HIV-Risk Behaviors and Social Support Among Men and Women Attending Alcohol-Serving Venues in South Africa: Implications for HIV Prevention

Abstract: Background Alcohol use is associated with increased HIV-risk behaviors, including unprotected sex and number of sex partners. Alcohol-serving venues can be places to engage in HIV-related sexual risk behaviors, but are also important sites of social support for patrons, which may mitigate risks. We sought to examine the relationship between alcohol-serving venue attendance, social support, and HIV-related sexual risk behavior, by gender, in South Africa. Methods Adult patrons (n=496) were recruited from six … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…As well, there are mixed findings concerning gender-specific relationship between social support and HIV risks. For example, a study of individuals attending venues serving alcohol in South Africa [42] found that social support was correlated with fewer sexual risk behaviors for females, but not for males. Contrarily, in a study of drug injection users in Sichuan, China [43], the researchers did not observe a relationship between social support and HIV risk behaviors among female users, but identified that decreased social support was correlated with increased HIV risk behaviors among male users.…”
Section: Introductionmentioning
confidence: 99%
“…As well, there are mixed findings concerning gender-specific relationship between social support and HIV risks. For example, a study of individuals attending venues serving alcohol in South Africa [42] found that social support was correlated with fewer sexual risk behaviors for females, but not for males. Contrarily, in a study of drug injection users in Sichuan, China [43], the researchers did not observe a relationship between social support and HIV risk behaviors among female users, but identified that decreased social support was correlated with increased HIV risk behaviors among male users.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have shown that women who frequent alcohol serving venues, like OFSW and OHRW, have an increased prevalence of psychosocial factors that can exacerbate HIV infection risk [14][15][16][17][18][19][20][21]. One study in South Africa found women who attended alcoholserving venues daily had more partners and more unprotected sex than those who didn't [22]. A study in Zimbabwe found that women at venues offering alcohol described more risky behaviors than those without alcohol [23].…”
Section: Discussionmentioning
confidence: 99%
“…AUD prevalence in South Africa is 7%, compared to 3.7% in other sub‐Saharan African countries [6,7], higher for men (12.4%) than for women (1.8%) and higher in rural than urban settings [8,9]. Patrons at shebeens, congregate settings where alcohol is served, report high‐risk behaviours making these an ideal setting for engaging young men for HIV prevention and treatment [10–12]. Pre‐exposure prophylaxis (PrEP) is a highly efficacious biomedical HIV prevention tool [13].…”
Section: Introductionmentioning
confidence: 99%